The Leadership Style Effect on Telecommunication Industries: A Systematic Review - M, Misbahudddin; Maarif, Mohammad Syamsul; Suroso, Arif Imam; Triyonggo, Yunus (Sekolah Tinggi Manajemen IPMI, 2025)
This study undertakes a comprehensive and systematic review of the influence of different leadership approaches within the telecommunication industry, a critical factor for organizational success. Using systematic literature review methods, it analyzed 51 articles from four databases across 24 countries. Among 27 leadership styles, there are two of the most studied leadership styles namely transformational and transactional leadership. In addition, newer leadership styles like strategic, agile, ambidextrous, level five, ethical, directive, participative, democratic, and smart leadership have gained attention. The research rigorously assesses how each style influences variables positively or negatively, focusing on the top five crucial aspects; organizational performance, employee creativity, organizational citizenship behavior, organizational culture, and employee performance. The telecommunications industry was chosen because of its rapid expansion, focus on technology, worldwide reach, and substantial economic influence. The industry's traits are closely associated with different styles of leadership. The study offers valuable insights into leadership style adoption in telecommunications and recommendations for further research.